Bruno Latours Soziologie der »Existenzweisen«: Einführung und Diskussion - Laux, Henning (transcript, 2016)
With his work »An Inquiry Into Modes of Existence: An Anthropology of the Moderns« (2013), Bruno Latour makes good on his promise to provide an alternative description of Western culture. He depicts modern conflicts of value and sketches out a diplomatic mission aimed at achieving a peace accord between cultures and salvation from the planetary climate catastrophe. With analyses on the different modes of existence – such as politics, economy, religion or technology – the contributors test the sociological content of Latour's findings and set them in relation with the preexisting body of knowledge. In this way, Latour's major work is not just critically inspected, but also openly debated in its entire scope for the first time.